Analisis Stabilitas pada Lereng Sungai yang Dipengaruhi Pasang Surut - Hamdhan, Indra Noer; Pratiwi, Desti Santi (Department of Civil Engineering, Diponegoro University, 2018)
The slopes on river banks close to the estuary can be affected by tides, so it can experience stability in the river bank. Therefore, this research is conducted to determine the stability of river bank due to tides with numerical analysis. The numerical analysis method was done by 2D Plaxis Software that using the Finite Element Method. The analysis was conducted on a homogeneous slope with 2 (two) different soil permeability coefficient values, there are low permeability and high permeability. The analysis is modeled by fully coupled analysis between deformation and ground water flow analysis. The results of the analysis indicate that a tidal are influence the stability of the slope based on the safety factor value. The highest of safety factor value are shown in high tide condition, and the lowest occur at low tide condition. This happens because the high tide condition occur the addition of hydraulic pressure from the water that will resist the sliding, while the low tide condition will reduce the hydraulic pressure. This can be a concern to the stability of river bank with tidal condition in order to avoid the erosion during the low tide conditions. The comparison of safety factors between two different types of soil permeability are not significant, the difference are only 3%.